Pembelajaran Matematika Berbasis Masalah dengan Strategi Inkuiri Terbimbing dan Bebas Termodifikasi Ditinjau Dari Kemampuan Awal siswa Kelas VII MTS Takmirul Islam Surakarta - Cahyani, Eko Diah, Prof. Dr. Bambang Sumardjoko, M.Pd, Dr. Sumardi, M.Si (2016)
The purpose of this study, there are three. (1) Test the effect difference of problem based learning strategies guided inquiry and modified free inquiry on student learning outcomes. (2) Test the effect difference early ability categories of high, medium and low student to student learning outcomes. (3) Test the interaction between early ability category strategy with high, medium and low student to student learning outcomes. This type of research is quantitative with quasi experiment Desai. The study population all students of class VII MTs Ta'mirul Islam Surakarta. The research sample two classes. The sampling technique is cluster random sampling by lottery. Data collection techniques with cognitive testing and documentation methods. Data were analyzed using analysis of variance of two different cell. The results of the study with α = 5%. (1) There are differences in the effect of problem-based learning strategies guided inquiry and modified free inquiry on student learning outcomes. (2) There are differences in the effect of the initial capabilities categories of high, medium and low student to student learning outcomes. (3) There is no interaction between early ability category strategy with high, medium and low student to student learning outcomes. Keywords: student learning outcomes, initial capabilities, guided inquiry, inquiry freely modified